Effect of sowing time, its pattern and fertility level on performance of CM 111-an inbred parental line of maize hybrid in winter season - SEN, AVIJIT; SINGH, SUBHASH CHANDRA; SHARMA, S N; SINGH, A K; PAL, A K (The Indian Journal of Agricultural Sciences, 2013)
A field trial was conducted during winter season (rabi) of 1995-96 and 1996-97 to study the response of maize inbred parental line CM 111 to sowing time (10, 20 and 30 November), fertility levels (50, 13.1, 16.67 and 3.5; 100,26.2, 33.34 and 7.0,150,39.3,50.01 and 10.5 kg/ha of N, P, K and Zn) and sowing pattern (60 cm x 25 cm, 50 cm x 20 cm and 50 cm x 15 cm). All the yield attributing characters except a few were significantly affected by dates of sowing, fertility levels and plant populations. Early sowing, higher doses of fertilizers and lower plant population recorded greater values for the yield attributing characters leading to greater seed yield. Sowing on 10 November gave 40.22 and 13.42% higher seed yield than 30 and 20 November of sowing respectively. F3 recorded 63.03 and 15.66% more yield than F1, and F2. The lowest plant population (S,) gave 24.28 and 11.28% more seed yield than S3 and S2’ respectively. In the functional relationship while seed yield was observed to have a negative linear relationship with date of sowing and plant population, was quadratic in case of fertility levels.